JAPANESE DIPLOMACY MAKES EW HEADWAY IN CENTRAL ASIA: ITS PROBLEMS, EXPECTATIONS, AND PROSPECTS - NURGALIEV, Marat; SHAYMERGENOV, Timur (CENTRAL ASIA AND THE CAUCASUS, 2007)
he geopolitical space of Central Eurasia has long been a wrestling ring for the leading global and regional players. During the fifteen years since the U.S.S.R. disintegrated, specific actors have taken up their position in this process, formulated their goals and interests, and drawn up explicit game rules. Japan did not previously feature on the list of powers taking part in the intensive geopolitical struggle in the region. Since the Central Asian states gained their independence, Japanese policy toward the Central Asian Region (CAR) was not distinguished by high activity. Nevertheless, in the past few years, this player has been showing increased interest in Central Asia, which was aroused by several political and economic factors. Japan appears to have noticeably activated its diplomatic resources recently for the explicit pur pose of enhancing its relations with the CAR countries. It is generally thought that Tokyo’s Central Asian diplomacy has its sights set on the energy resources it requires for guaranteeing Japan’s energy security against the background of the steadily mounting price of oil. As we know, Tokyo is currently carrying out a new energy strategy aimed at ensuring long-term stable deliveries of oil, gas, and other energy resources in order to boost its economy, which is the second largest in the world. But if we look closer, it becomes clear that Japan is trying to play an even greater geopolitical role. In so doing, Japanese ambitions are aimed not only at Central Asia, but at Eurasia as a whole—in counterbalance to the growing influence of Moscow and Beijing, as well as, most likely, under Washington’s patronage, the Land of the Rising Sun being its long-standing and devoted ally.